Influence of Water Content on the Mechanical Characteristics of Mudstone with High Smectite Content - Feng Chen; Xiaoming Sun; Hao Lu (Geofluids)
Water content plays an important role in strength of mudstone; many works pay more attention to the strength of dry and saturated rocks. In this study, the water absorption characteristics of mudstone were obtained by a computer-automated WA (water absorption) equipment system experiments. The complete stress–strain curves and UCS (unconfined compress strength) and E (Young’s modulus) of mudstone samples under different water contents were achieved by using the WEP-600 microcomputer-control screen universal testing machine. SEM (scanning electron microscope) test were carried out to study the microstructure characteristics of mudstone samples under different water contents. The results showed that the water absorption process of mudstone consists of three stages. The UCS and E of the mudstone samples markedly decrease with water content increasing. Based on the experimental results and analysis, a porous medium mechanical model of the mudstone was established and a deeper understanding of water-induced strength damage mechanism of the mudstone was achieved.